2023
DOI: 10.3389/fnut.2023.1119768
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of intestinal microbiota in infants with late-onset breast milk jaundice

Qianying Guo,
Xinran Liu,
Mingxuan Cui
et al.

Abstract: IntroductionIn this paper, microbiota analysis was determined to analyze the structure and difference of intestinal microbiota between LBMJ (late-onset breast milk jaundice) infants and healthy individuals.MethodsWe collected fresh fecal samples from 13 infants with LBMJ and 13 healthy individuals, then determined the intestinal microbiota by 16 s rRNA sequencing. The differences of microbiota structure, diversity and functional characteristics between the two groups were analyzed, and the correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…These data indicate that the gut microbiota are important participants in the bilirubin metabolism. An increase in diversity and abundance is a common manifestation of gut microbiota disorders in NH (17,18). The present study found that 24 h of phototherapy markedly reduced the diversity and abundance of intestinal flora, suggesting that phototherapy may also partially reverse the microflora changes caused by NH.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These data indicate that the gut microbiota are important participants in the bilirubin metabolism. An increase in diversity and abundance is a common manifestation of gut microbiota disorders in NH (17,18). The present study found that 24 h of phototherapy markedly reduced the diversity and abundance of intestinal flora, suggesting that phototherapy may also partially reverse the microflora changes caused by NH.…”
Section: Discussionsupporting
confidence: 59%
“…S. salivarius can release bacteriocins (salivary A5 and B) (23-25), thereby antagonizing opportunistic or pathogenic bacteria. As aforementioned, the diversity and abundance of the gut microbiota in newborns with hyperbilirubinemia are increased and contain a number of opportunistic pathogens (17,18). Therefore, the increase in the abundance of S. salivarius after phototherapy may partially improve intestinal defense function.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, младенцы сравниваемых групп различались по уровням глицериновой и янтарной кислот, а также фенилаланина [31]. Дети с желтухой грудного молока отличаются от детей без желтухи альфа-и бетаразнообразием микробиоты, и в частности большим количеством микробов рода Klebsiella, что, по мнению авторов исследования, ведет к увеличению активности ␤-глюкуронидазы в кишечнике и таким образом способствует развитию желтухи грудного молока [40]. Следует учитывать, что в последнее исследование включены дети с поздней манифестацией желтухи грудного молока, то есть особенности микробиоты могли быть частично обусловлены возрастом детей.…”
Section: роль кишечной микробиотыunclassified